Improving the operational performance of two-quadrant parclo interchanges with median U-turn concept. Issue 3 (3rd July 2018) - Zhao, Jing; Ma, Wanjing; Head, K. Larry; Han, Yin
ABSTRACT: Parclo (partial cloverleaf) interchange, connecting major freeways and surface streets with one or two loop ramps and two closely spaced intersections, is one of the most commonly used interchange types in urban and suburban areas. The two-ramp terminal intersections are often the critical bottlenecks for the parclo interchange system, especially when the turning volumes are high. In this study, we propose a design in which the median U-turn technology is applied to the parclo interchanges to relieve the congestion problem. A mixed-integer nonlinear program is developed to integrate the selection of prohibited movements with detour routes, lane markings, and signal timings for three types of parclo interchange. The results from extensive numerical analyses and a case study reveal that the proposed design is promising as it could increase the capacity. The capacity improvement, when the proposed design is applied, is larger with the increase in the proportion of the turning movements. Moreover, a relatively stable capacity improvement (approximately 8.33%) could be obtained when our design is applied to cases where the volumes between the two sub-intersections are unbalanced.